PRENATAL BIOCHEMICAL SCREENING: MARKERS, EVIDENCE AND PRACTICE (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
Prenatal biochemical screening represents one of the most dynamically developing fields of modern perinatal medicine. Its fundamental objective is the early identification of pregnant women at elevated risk of fetal chromosomal anomalies, structural malformations, and obstetric complications in order to facilitate timely clinical decision-making and optimise antenatal management. Contemporary screening programmes are based on the measurement of specific biological molecules produced by the fetoplacental unit or released into the maternal circulation in response to ongoing gestation, the concentration of which undergoes characteristic and predictable alterations in the presence of pathological conditions.
Keywords: biochemical screening, prenatal diagnosis, PAPP-A, free β-hCG, AFP, cell-free DNA, chromosomal anomalies, trisomy 21